2015
DOI: 10.1200/jco.2014.60.6624
|View full text |Cite
|
Sign up to set email alerts
|

Limited Resection Versus Lobectomy for Older Patients With Early-Stage Lung Cancer: Impact of Histology

Abstract: We found generally that limited resection is not equivalent to lobectomy in older patients with invasive non-small-cell lung cancer ≤ 2 cm in size, although segmentectomy may be equivalent in patients with adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 45 publications
3
66
0
1
Order By: Relevance
“…Limited resection is not adequate for patients with lymph node involvement. Similar to our results, Veluswamy and colleagues (27) identified stage IA invasive adenocarcinoma and squamous cell carcinoma with tumor size ≤2 cm among patients older than 65 years. They indicated that limited resection, particularly wedge resection, did not lead to equivalent outcomes as lobectomy.…”
Section: Discussionsupporting
confidence: 81%
“…Limited resection is not adequate for patients with lymph node involvement. Similar to our results, Veluswamy and colleagues (27) identified stage IA invasive adenocarcinoma and squamous cell carcinoma with tumor size ≤2 cm among patients older than 65 years. They indicated that limited resection, particularly wedge resection, did not lead to equivalent outcomes as lobectomy.…”
Section: Discussionsupporting
confidence: 81%
“…Our data also showed that these two surgical options might not result in similar survival rates in elderly patients (≥65 years old). This was in accord with Veluswamy's study, which also pointed out that differences might arise in elderly patients, depending on the different histology subgroups (29). In contrast, both segmentectomy and lobectomy could be optional for younger patients.…”
Section: Discussionsupporting
confidence: 77%
“…Two other retrospective reviews comparing limited resection and lobectomy in stage I or II patients demonstrated a trend towards improved recurrence rate and OS in the lobectomy group that did not reach statistical significance (6,7). Other work has highlighted the potential importance of histology in tumors ≤2 cm, with lobectomy being associated with superior survival in squamous cell carcinoma compared to wedge resection or segmentectomy, and segmentectomy demonstrating equivalent survival to lobectomy in adenocarcinoma (8). Finally, a recent review of the National Cancer Database indicated that lobectomy was associated with improved OS, adequate lymphadenectomy rate, and negative margin rate (9).…”
mentioning
confidence: 99%